PSIKOLINGUISTIK PEMBELAJARAN HURUF HIJAIYAH: ASOSIASI KATA (BERBASIS KLU) DAN DAYA INGAT ANAK USIA DINI - Muhammad Arifin Ilham; Tatang (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study discusses the application of clue-based word association methods in the learning of hijaiyah letters for early childhood, specifically ages 4-5 years. The purpose of the research is to explore the influence of word-based clues on children's memory in recognizing hijaiyah letters and to identify the psycholinguistic factors that affect the success of the learning process. The research uses a descriptive qualitative approach with observational techniques at a tutoring center for learning hijaiyah letters. The research results show that the use of clues based on familiar words, such as